2021
DOI: 10.1177/11206721211001266
|View full text |Cite
|
Sign up to set email alerts
|

Very late orbital recurrence of choroidal melanoma four decades post enucleation

Abstract: Orbital recurrence of malignant choroidal melanoma is quite uncommon, occurring in about 3% of patients undergoing enucleation for large tumors. Orbital recurrences after more than 10 years from enucleation are even rarer. In literature, only few reports described orbital recurrence that occurred between 10 and 40 years after primary diagnosis. Herein we report a very late choroidal melanoma recurrence, 40 years post enucleation, of a 52 year-old female who had undergone left enucleation at the age of 12. She … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Local recurrence of uveal melanoma is most frequently of the mixed cell type, 7 , 9 , 12 as seen in our patient. The advent of tumor genetic profiling has enabled molecular characterization of uveal melanomas and the potential derivation of insights into their pathophysiology.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Local recurrence of uveal melanoma is most frequently of the mixed cell type, 7 , 9 , 12 as seen in our patient. The advent of tumor genetic profiling has enabled molecular characterization of uveal melanomas and the potential derivation of insights into their pathophysiology.…”
Section: Discussionsupporting
confidence: 59%
“… 11 The presence of extrascleral extension does not seem to correlate with the time from enucleation to local recurrence, 7 which can vary widely from 3.5 months 7 to 40 years. 12 It is worth noting that our patient had no histologic evidence of extrascleral extension or optic nerve invasion at time of enucleation. Similarly, Sanke et al reported two patients with local recurrence of uveal melanoma after enucleation who did not have histological evidence of extrascleral extension.…”
Section: Discussionmentioning
confidence: 63%